2022
DOI: 10.1101/2022.04.13.488155
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Perceptual expectations and false percepts generate stimulus-specific activity in distinct layers of the early visual cortex

Abstract: Popular theories suggest that hallucinations arise through excessive top-down perceptual expectations, whereas others have emphasised the role of spontaneous bottom-up activity. These theories make different predictions about how input and feedback layers in sensory regions contribute to hallucinations. Here, we used layer-specific fMRI to interrogate neural activity underlying hallucinations - high confidence false percepts - and perceptual expectations while healthy participants (N=25) performed a perceptual… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 96 publications
(190 reference statements)
2
10
0
Order By: Relevance
“…In both samples, there was no evidence for a relationship between the strength of content predictions and hallucination-proneness. This is in line with previous studies where content cues were not associated with hallucination-like perception (Haarsma et al, 2023). In contrast, in the discovery sample we did find that presence predictions have an enhanced influence on confidence in stimulus presence on absent trials, suggesting that presence priors are indeed overly strong.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In both samples, there was no evidence for a relationship between the strength of content predictions and hallucination-proneness. This is in line with previous studies where content cues were not associated with hallucination-like perception (Haarsma et al, 2023). In contrast, in the discovery sample we did find that presence predictions have an enhanced influence on confidence in stimulus presence on absent trials, suggesting that presence priors are indeed overly strong.…”
Section: Discussionsupporting
confidence: 93%
“…The lack of an overly strong prediction effect in people prone to hallucinations in the replication sample seemingly contradicts the past literature. Although some past studies have found this type of effect in similarly sized or smaller, normative samples (Haarsma et al, 2023; Stuke et al, 2021), larger sample sizes may be required to observe these effects consistently. Furthermore, it is important to note that the average CAPS scores in this study were considerably lower (averaging around 45, in line with the original study by Bell et al, 2005) compared to some previous studies, which reported average CAPS scores of 107 (Stuke et al, 2021), 72 (Haarsma et al, 2023) and 58 (Schmack et al, 2021).…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Layer specific neuroimaging techniques would be required for empirical verification, providing a promising avenue for future research (Haarsma, Kok, et al, 2022). Interestingly, recent research found that high confidence false percepts (a measure of hallucinatory propensity) were related to stimulus-like activity in middle input layers of the visual cortex in healthy participants (Haarsma, Deveci, et al, 2022). Task measures of hallucination propensity were also found to be associated with everyday hallucination severity, suggesting that hallucinatory-like perception may arise from spontaneous bottom-up activity in input layers of the visual cortex.…”
Section: Discussionmentioning
confidence: 99%